2022
DOI: 10.2459/jcm.0000000000001362
|View full text |Cite
|
Sign up to set email alerts
|

Role of computed tomography in transcatheter replacement of ‘other valves’: a comprehensive review of preprocedural imaging

Abstract: Transcatheter procedures for heart valve repair or replacement represent a valid alternative for treating patients who are inoperable or at a high risk for open-heart surgery. The transcatheter approach has become predominant over surgical intervention for aortic valve disease, but it is also increasingly utilized for diseases of the ‘other valves’, that is the mitral and, to a lesser extent, tricuspid and pulmonary valve. Preprocedural imaging is essential for planning the transcatheter intervention and compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
(227 reference statements)
0
3
0
Order By: Relevance
“…Additional MPR planes parallel to the TV can optimize the visualization of the TV leaflets anatomy and identification of a four-leaflet configuration variant, which is associated with an increased risk of residual TR, especially in patients with a wide coaptation gap or TR jet from the posteroseptal or anteroposterior commissures [36]. It also allows the measurement of the position and extent of the coaptation gap and TV leaflet tethering grade, including tenting height, angle, and area, which is always measured in mid-systole; by aligning the reformation planes with the narrowest portion of the regurgitant orifice during mid-systole, is possible to measure the anatomical regurgitant orifice area, which may represent a flow-independent anatomic parameter of TR severity [35,[37][38][39]. CCT may provide useful information on TV and leaflet anatomy, the valve gap, mechanisms of TR, and the best fluoroscopic angles for coplanar alignment and leaflet grasping strategy [32,34].…”
Section: Cardiac Computed Tomographymentioning
confidence: 99%
“…Additional MPR planes parallel to the TV can optimize the visualization of the TV leaflets anatomy and identification of a four-leaflet configuration variant, which is associated with an increased risk of residual TR, especially in patients with a wide coaptation gap or TR jet from the posteroseptal or anteroposterior commissures [36]. It also allows the measurement of the position and extent of the coaptation gap and TV leaflet tethering grade, including tenting height, angle, and area, which is always measured in mid-systole; by aligning the reformation planes with the narrowest portion of the regurgitant orifice during mid-systole, is possible to measure the anatomical regurgitant orifice area, which may represent a flow-independent anatomic parameter of TR severity [35,[37][38][39]. CCT may provide useful information on TV and leaflet anatomy, the valve gap, mechanisms of TR, and the best fluoroscopic angles for coplanar alignment and leaflet grasping strategy [32,34].…”
Section: Cardiac Computed Tomographymentioning
confidence: 99%
“…27 CT is also crucial for the success of transcatheter valve replacement, allowing a complete evaluation of mitral and tricuspid apparatus and biventricular anatomy. 28 Although the 2019 Guidelines on chronic coronary syndrome (CCS) of the European Society of Cardiology changed the current management of affected patients, they could not clarify which type of test, functional or anatomic, should be first chosen in different clinical scenarios of suspected CCS. 29 Stress-echocardiography can rightly be considered very useful, due to its real-time imaging, high temporal resolution, safety, absence of radiation and low cost.…”
mentioning
confidence: 99%
“…It has also been shown that psoas muscular attenuation CT measurement (mean HU and high-density/low-density muscle) are independent and incremental predictors of all-cause mortality in patients undergoing TAVI 27 . CT is also crucial for the success of transcatheter valve replacement, allowing a complete evaluation of mitral and tricuspid apparatus and biventricular anatomy 28 …”
mentioning
confidence: 99%